Neonatal death prediction scores: a systematic review and meta-analysis - Felipe C S Veloso; Carine R A Barros; Samir B Kassar; Ricardo Q Gurgel (BMJ Paediatrics Open)
Objective To compare, through a systematic review and meta-analysis of observational accuracy studies, the main existing neonatal death prediction scores.Method Systematic review and meta-analysis of observational accuracy studies. The databases accessed were MEDLINE, ELSEVIER, LILACS, SciELO, OpenGrey, Open Access Thesis and Dissertations, EMBASE, Web of Science, SCOPUS and Cochrane Library. For qualitative analysis, Quality Assessment of Diagnostic Accuracy Studies 2 was used. For the quantitative analysis, the area under the curve and the SE were used, as well as the inverse of the variance as a weight measure, DerSimonian and Laird as a measure of random effects, Higgins’ I² as an estimate of heterogeneity, Z as a final measure with a 95% confidence level.Results 55 studies were analysed, 8 scores were compared in a total of 193 849 newborns included. The most accurate neonatal death prediction score was Score for Neonatal Acute Physiology Perinatal Extension II (SNAPPE II) (0.89 (95% CI 0.86 to 0.92)) and the least accurate was gestational age (0.75 (95% CI 0.71 to 0.79)).Conclusion SNAPPE II was the most accurate score found in this study. Despite this, the choice of score depends on the situation and setting in which the newborn is inserted, and it is up to the researcher to analyse and decide which one to use based on practicality and the possibility of local implementation. Given this, it is interesting to carry out new prospective studies to improve the prediction of neonatal deaths around the world.PROSPERO registration number CRD42023462425.